Catalase Expression in Azospirillum brasilense Sp7 Is Regulated by a Network Consisting of OxyR and Two RpoH Paralogs and Including an RpoE1→RpoH5 Regulatory Cascade - Rai, Ashutosh Kumar (Appl Environ Microbiol, 2018)
The genome of Azospirillum brasilense encodes five RpoH sigma factors: two OxyR transcription regulators and three catalases. The aim of this study was to understand the role they play during oxidative stress and their regulatory interconnection. Out of the 5 paralogs of RpoH present in A. brasilense, inactivation of only rpoH1 renders A. brasilense heat sensitive. While transcript levels of rpoH1 were elevated by heat stress, those of rpoH3 and rpoH5 were upregulated by H(2)O(2). Catalase activity was upregulated in A. brasilense and its rpoH::km mutants in response to H(2)O(2) except in the case of the rpoH5::km mutant, suggesting a role for RpoH5 in regulating inducible catalase. Transcriptional analysis of the katN, katAI, and katAII genes revealed that the expression of katN and katAII was severely compromised in the rpoH3::km and rpoH5::km mutants, respectively. Regulation of katN and katAII by RpoH3 and RpoH5, respectively, was further confirmed in an Escherichia coli two-plasmid system. Regulation of katAII by OxyR2 was evident by a drastic reduction in growth, KatAII activity, and katAII::lacZ expression in an oxyR2::km mutant. This study reports the involvement of RpoH3 and RpoH5 sigma factors in regulating oxidative stress response in alphaproteobacteria. We also report the regulation of an inducible catalase by a cascade of alternative sigma factors and an OxyR. Out of the three catalases in A. brasilense, those corresponding to katN and katAII are regulated by RpoH3 and RpoH5, respectively. The expression of katAII is regulated by a cascade of RpoE1→RpoH5 and OxyR2. IMPORTANCE In silico analysis of the A. brasilense genome showed the presence of multiple paralogs of genes involved in oxidative stress response, which included 2 OxyR transcription regulators and 3 catalases. So far, Deinococcus radiodurans and Vibrio cholerae are known to harbor two paralogs of OxyR, and Sinorhizobium meliloti harbors three catalases. We do not yet know how the expression of multiple catalases is regulated in any bacterium. Here we show the role of multiple RpoH sigma factors and OxyR in regulating the expression of multiple catalases in A. brasilense Sp7. Our work gives a glimpse of systems biology of A. brasilense used for responding to oxidative stress.